Gamificação no ensino de operações matemáticas - Morais, Rodrigo de (2018)
There is a great chasm in the quality of Brazilian education compared to other countries. Among the disciplines where the results are most alarming is mathematics, with the use of methodologies that may often be old and not attractive to the new generations, however, one observes the constant and growing use of technological resources and tools aimed at the education. At some point this connection is lost and often does not arrive in the classroom, in that sense and to avoid these deviations in the use of technology, and generate a greater commitment on the part of the students, the active methodologies were developed. In the work will be approached the concepts of gamification, the use of mechanisms found in games as challenges and rewards, with the intention of engaging and encouraging students to develop activities. These concepts were applied in a game developed to aid in the teaching of the four basic math operations, codename Knight Math.